2016
DOI: 10.1158/1078-0432.ccr-15-2568
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of 149 Salivary Duct Carcinomas, Carcinoma Ex Pleomorphic Adenomas, and Adenocarcinomas, Not Otherwise Specified Reveals Actionable Genomic Alterations

Abstract: CGP of salivary adenocarcinoma, NOS, SDCs, ca ex PA, and carcinoma, NOS revealed diverse GAs that may lead to novel treatment options. Clin Cancer Res; 22(24); 6061-8. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 52 publications
5
120
3
Order By: Relevance
“…In salivary tumours, p53 mutations are commonly identified, and that identification is consistent in cxpa 20 . Anomalies in cyclin-dependent kinases and inhibitors cox2 and fgf2 have also been identified in other studies [21][22][23] . Although potential targets have been identified (MYC, HMGA2, MDM2, COX2, and FGF2) for which inhibitors are in development, none has been reported as attempted for patient management.…”
Section: Discussionsupporting
confidence: 61%
“…In salivary tumours, p53 mutations are commonly identified, and that identification is consistent in cxpa 20 . Anomalies in cyclin-dependent kinases and inhibitors cox2 and fgf2 have also been identified in other studies [21][22][23] . Although potential targets have been identified (MYC, HMGA2, MDM2, COX2, and FGF2) for which inhibitors are in development, none has been reported as attempted for patient management.…”
Section: Discussionsupporting
confidence: 61%
“…More importantly, 91.5% of these patients had at least one aberration that was potentially targetable by an FDAapproved drug or an investigational agent in a clinical trial, showing that research on targeted therapies based on molecular profiling is worthwhile [81]. A study of 149 patients also had similar results, with further alterations in RAS, ERBB2, NOTCH1, NF1, and RET, showing diverse genetic alterations that may lead to novel treatment options [69]. The molecular targets and the signaling pathways activated by the previously described translocations for MEC, AdCC, and SC are also of potential therapeutic use.…”
Section: Clinical Relevance Of Heterogeneitymentioning
confidence: 88%
“…In addition, ERBB2 overexpression and amplification similar to those which occur in SDC [68,69], copy number gains involving 9p23-p22.3 (NFIB) and 22q12-qter (PDGFB) [70], MDM2 amplification [71,72], loss of heterozygosity, and microsatellite alterations in the p53 and RB genes and at chromosomal location 5q [73] are all secondary genetic alterations detected in CPA and may be of importance for disease progression from PA.…”
Section: Pa and Its Progression: An Example Of Recurrent Genetic Altementioning
confidence: 99%
“…One of the most frequently altered pathways is the PI3K/AKT/mTOR pathway, with many SDC specimens showing mutations and copy number variations in PIK3CA , PTEN , RICTOR , AKT1 , AKT3 , and/or PIK3R1 [5760]. As with other tumor types, TP53 mutations, HRAS/NRAS mutations and alterations in cyclin D1/CDK pathways are also found with relative frequency in SDC [4, 50, 57, 59, 61, 62]. A few studies have demonstrated loss of p16 expression [3, 4, 18].…”
Section: Mutational Landscape Of Sdcmentioning
confidence: 99%
“…A few studies have demonstrated loss of p16 expression [3, 4, 18]. Combinations of alterations in more than one of these pathways is also relatively common in SDC [50, 57, 61]. Other less common gene expression patterns and genomic alterations have been found in small numbers of studies including few tumors, and their significance is unclear [3, 27, 31, 50, 61, 6367].…”
Section: Mutational Landscape Of Sdcmentioning
confidence: 99%